2012
DOI: 10.1016/s2221-1691(12)60055-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hepatoprotective activity of Cyathea gigantea (Wall. ex. Hook.) leaves against paracetamol–induced hepatotoxicity in rats

Abstract: The methanolic extract of leaves of C. gigantea at doses of 100 mg/kg bw and 200 mg/kg bw have significant effect on liver of paracetamol induced hepatotoxicity model in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The dose of APAP was selected based on Kiran et al [19]. Twenty-four hours after the APAP ingestion, the rats in PML and PMH groups were received P. major extract 1 000 mg/kg and 1 500 mg/kg respectively, and the NAC (900 mg/kg) for the NAC group.…”
Section: Induction Of Liver Toxicity and Tissue Collectionmentioning
confidence: 99%
“…The dose of APAP was selected based on Kiran et al [19]. Twenty-four hours after the APAP ingestion, the rats in PML and PMH groups were received P. major extract 1 000 mg/kg and 1 500 mg/kg respectively, and the NAC (900 mg/kg) for the NAC group.…”
Section: Induction Of Liver Toxicity and Tissue Collectionmentioning
confidence: 99%
“…During respectively. The in-vitro and in-vivo antioxidant activity assay suggest the ability of CEE extract to reduce biological oxidative stress [25]. Hepatoprotective activity of CEE extract may also be acquired by scavenging the free radicals against oxidative stress [26].…”
Section: Discussionmentioning
confidence: 99%
“…[20] showed that the aqueous extract L. nepetifolia, given as chronic post-treatment, protected against CCl 4 -induced hepatic damage in rats in a similar manner. Additionally, several studies have shown that the methanol and aqueous extracts of some medicinal plants protect against APAPinduced hepatotoxicity by abrogating the drug-induced increase in liver enzymes and maintaining normal liver morphology [21][22][23][24]. Several studies have identified antioxidant phytochemicals, such as polyphenols and flavonoids, which were suggested to be responsible for the medicinal plants' protective properties against APAP-induced hepatic injury [25][26][27][28].…”
Section: Pre-treatment and Post-treatment Effects Of Extracts On Hepamentioning
confidence: 99%